Multiculturalismo e o problema da universalidade: uma análise das teorias de Charles Taylor e Will Kymlicka - Camati, Odair (Universidade do Vale do Rio dos Sinos, 2018)
In this work, I support the thesis that even though the encounter between Charles Taylor’s and Will Kymlicka’s theories offers good prospects for the establishment of a multicultural project in liberal and democratic societies, it has some limits when we try to universalize it. The difficulties regarding universalization are presented in different ways by the aforementioned authors. On the one hand, Kymlicka’s liberalism holds that the traditional values of liberalism are sufficient for the recognition of all different cultural manifestations. On this view, the universality would be preconceived, which, according to our understanding, would preclude a constructive dialogue with those who do not share the same values. On the other hand, Taylor proposes a model of practical reason with hermeneutical roots that would provide elements for the establishment of value judgments valid for all human communities that put themselves in a process of mutual understanding. The limitations of this model lie in the difficulty of establishing minimum conditions for this process to be developed without distortions. To get this point, we shall first take up the main elements involved in multicultural discussions in order to prove the need to discuss such issues. After that, we shall critically expose the conceptual foundations developed by both Canadian philosophers in their theories of multiculturalism. Basically, while autonomy is Kymlicka’s core concept, recognition is Taylor’s one. Finally, from a soft liberalism, which claims the lack of state neutrality and the valorization of the context of choice, we propose that the encounter between the two theories has enough elements to develop a multicultural project in societies that are both liberal and democratic. Yet this does not necessarily mean that we have elements for a multicultural project with universal validity.
Keywords: Multiculturalismo; Universalidade; Autonomia; Reconhecimento; Charles Taylor; Will Kymlicka; Multiculturalism; Universality; Autonomy; Recognition; Charles Taylor; Will Kymlicka; ACCNPQ::Ciências Humanas::Filosofia